2019
DOI: 10.1021/acs.chemmater.9b01886
|View full text |Cite
|
Sign up to set email alerts
|

Noncovalent Close Contacts in Fluorinated Thiophene–Phenylene–Thiophene Conjugated Units: Understanding the Nature and Dominance of O···H versus S···F and O···F Interactions with Respect to the Control of Polymer Conformation

Abstract: Using a simple π-conjugated trimer, EDOT-phenylene-EDOT (where EDOT = 3,4-ethylenedioxythiophene), we evaluate the effect that fluorine substituents have upon changes in conformation, conjugation and oxidation potentials in π-conjugated structures. These variations are assessed as a function of the fluorine atom's propensity to feature in hydrogen and/or halogen bonding with other heteroatoms. The molecular motif was chosen because the EDOT unit presents the possibility of competing O•••X or S•••X non-covalent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 50 publications
(90 reference statements)
4
34
0
Order By: Relevance
“…Overall, these results are supported by previous empirical findings, [58, 59] and the quantification paves the way for rational exploitation of substituents in a wide range of molecular designs.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Overall, these results are supported by previous empirical findings, [58, 59] and the quantification paves the way for rational exploitation of substituents in a wide range of molecular designs.…”
Section: Resultssupporting
confidence: 86%
“…Nonetheless,a lignment of the side-chains in the solid state may occasionally contribute to the planarization of the conjugated backbone through packing effects. [57] Overall, these results are supported by previous empirical findings, [58,59] and the quantification paves the way for rational exploitation of substituents in aw ide range of molecular designs.…”
Section: Angewandte Chemiesupporting
confidence: 83%
“…crystallinity and facilitate charge transport. [22][23][24][25][26][27][28] Moreover, comparing the 1,1-dicyanomethylene-3-indanone (IC) endgroup with its fluorinated derivative 2-(5,6-difluoro-3oxo-2,3-dihydro-1H-inden-1-ylidene)malononitrile (IC-4F), the stronger electron-withdrawing effect of the latter can enhance intramolecular charge transfer (ICT) in NFA materials resulted in a red-shift of the absorption spectra of NFAs to the near-IR region, thus enhancing device photocurrent. Several studies have demonstrated that OSCs based on ladder type NFAs with fluorinated endgroups show improved device performance than those based on non-fluorinated counterparts.…”
Section: Intramolecular Interactions Through Noncovalent C−f•••s and mentioning
confidence: 99%
“…In fact, while there are several studies in the literature that have utilized ssNMR to characterize blend morphologies for polymers or polymer:fullerene blends, [23,[31][32][33][34][35][36][37] the application of ssNMR techniques to characterize structurally similar polymer:NFA blends is limited. [11,38] While fluorination in conjugated systems has been shown to result in improved molecular level interactions and charge transport by many previous reports, [29,[39][40][41] this is the first time that crucial differences such as π-π interactions and local ordering in polymer:NFA blends could also be resolved via ssNMR. Here, we posit that low energetic offset polymer:NFA systems with low voltage losses are key in attaining high PCEs -but not without a caveat.…”
Section: Introductionmentioning
confidence: 99%